Sou o que pareço, ainda assim não me conheço: articulações entre a Pedagogia Griô e o ensino de artes na Educação de Jovens e Adultos - Domingues, Rachel Maria (2020)
This dissertation analyzes how the practice of community education Pedagogia Griô articulates with the teaching of theatrical art through a methodological and experiential dialogue, resulting in a pedagogical action applied to a focus group of students of Youth and Adult Education (EJA), from a public school in the municipality of Cabedelo - PB. In this context, investments in observing whether, through the application of this reflex action, there was a movement to strengthen the cultural identity of the focus group, by a greater participation in school activities, by a greater involvement of these students involved in the research, without regard to the appreciation of local culture, which translates into meaningless affirmative and purposeful actions by the sabers and those who make these individuals in their community. Use participant observation as the qualitative research methodology. Thus, an analysis of the subjects' oral and corporate discourses during the experiences heard is verified by means of data collection instruments, conversation circles, audio and voice recording, semi-structured interviews, oral testimonies and data recorded in the field diary. The analyzes undertaken during the research screening in which the same were inferred, history of cultural difficulties in working with a Performing Arts discipline in the Teaching of Youth and Adults - EJA of the research field school, and engaging with the experiential practices of Griô Pedagogy, adopting the power as stories and ancestral roots of students, it was possible to observe the importance of recognition by the subjects exposed to their own history and culture, that is, their cultural identity.